Electrospinning of pure polymer-derived SiBCN nanofibers with high yield. Issue 8 (15th April 2021) - Chen, Qingqing; Jia, Dechang; Liang, Bin; Yang, Zhihua; Zhou, Yu; Li, Daxin; Riedel, Ralf; Zhang, Tao; Gao, Chenguang
Abstract: In this paper, we have discussed the synthesis of nanoscale silicoboron carbonitride (SiBCN) nanofibers by electrospinning of novel polyborosilazane precursor solutions, which were synthesized from boron trichloride, tris(dichloromethylsilylethyl)borane and hexamethyldisilazane using a one-pot method, followed by pyrolysis at 1000 °C under nitrogen atmosphere. The influence of the processing procedure (solution concentration, feeding rate and spinning voltage) of the electrospum fibers was also investigated. TGA and FT-IR experiments were employed to study the polymer-to-ceramic conversion and SEM was used to characterize the final materials. Combining the precursor derived ceramics route and electrospinning process enables to product SiBCN nanofibers for industrial applications.